Design & development of microorganism activity monitoring transducer using ultrasonic sensors - Aini Salwa Hasan Nudin (School of Mechatronic, Universiti Malaysia Perlis, 2011)
This thesis presents the design and development of a microorganism activity monitoring transducer by using ultrasonic sensors as the main part in detecting the signal of microrganism activity.